Strategies Of Responding To Praise Used By Hasanuddin University Students: Sociopragmatic Analysis - Herlisa Herlisa; Lukman Lukman; Gusnawaty Gusnawaty (Eduvest - Journal of Universal Studies, 2022)
This study aims to analyze the strategies for responding to praise used by Hasanuddin University students. This research is a qualitative research using descriptive method and the approach used in this research is a socio pragmatic approach. The data from this study were obtained from questionnaires distributed by researchers. After the data was obtained, the researcher analyzed the answers from the respondents using 12 praise response strategies according to Holmes, after which they were linked to the theory of praise indicators from Golato. The results in this study, namely the respondents in this study tend to accept the praise given and the most widely used praise response strategy is Strategy 1, namely Appreciation Token, Strategy 2 is Comment Acceptance and Strategy 3 is Praise Upgrade. Between the three ethnic backgrounds (Makassar, Bugis and Toraja) and the two sex groups (Male and Female), there was no significant difference in the choice of strategies to receive praise (Use of strategies 1, 2 and 3). Among the three categories of familiarity level, respondents tend to receive praise and use Strategy 1 (Appreciation Token) the most when meeting foreigners compared to using strategy 2 or strategy 3 where both of these strategies are used quite a lot (besides strategy 1) to provide an acceptance response a compliment delivered by a friend or friend